인체공학적 패턴 교육을 위한 새로운 교수법 제안: 3D 모델링 기반으로 제작한 Half Scale Body Form를 이용하여 - 천린; Lin Chen; 홍유화; Yuhwa Hong; 박주연; Juyeon Park (Fashion & textile research journal, 2024)
This study aimed to propose an innovative teaching pedagogy using a half-scale body form in apparel design education and evaluate its effectiveness in augmenting students’ understanding of ergonomic patterns. Constructed in alignment with Phoenix’s (2018) study, which used 3D body scanning and digital editing software, the half-scale body form was created through a five-step process, encompassing body measurement, 3D body modeling, fabrication of a physical half-scale body form, pattern making, and evaluation. Implemented in an undergraduate patternmaking course offered at a 4-year university in the metropolitan Seoul, this instructional approach’s effectiveness was gauged through students’ course projects and exit interviews. The results underscored the positive impact of the proposed teaching pedagogy on students’ grasp of ergonomic pattern development, fostering a keen understanding of diverse body shapes and sizes and the relationship between the human body and garments. Furthermore, it played a role in cultivating positive body image and self-endorsement among students. The research contributes meaningfully by presenting a fresh perspective in apparel design education, seamlessly integrating advanced anthropometric and technological tools into a conventional patternmaking classroom. It offers a novel learning experience for students majoring in apparel, creating a fun and interactive teaching environment.